Molecular Weight and Structural Properties of Biodegradable PLA Synthesized with Different Catalysts by Direct Melt Polycondensation - Hyung Woo Lee; Rizki Insyani; Daniel Prasetyo; Hermawan Prajitno; Johnner P. Sitompul (Journal of Engineering and Technological Sciences, 2015)
Production of biodegradable polylactic acid  (PLA)  from biomassbased lactic acid is widely studied for substituting petro-based plastics  or polymers. This study investigated PLA production from commercial lactic acid in a batch reactor by applying a direct melt polycondensation method with two kinds of catalyst,  Î³-aluminium(III)  oxide  (Î³-Al2O3) or  zinc oxide (ZnO),  in reduced pressure. The molecular weight of the synthesized PLA was determined by capillary viscometry and its structural properties were analyzed by functional group analysis using FT-IR. The yields of polymer production with respect to the theoretical conversion were 47% for Î³-Al2O3 and 35% for ZnO. However, the PLA from ZnO had a higher molecular weight (150,600 g/mol) than that from Î³-Al2O3 (81,400 g/mol). The IR spectra of the synthesized PLA from both catalysts using polycondensation show the same behavior of absorption peaks at wave numbers from 4,500 cm-1 to 500 cm-1, whereas the PLA produced by two other polymerization methods "“ polycondensation and ring opening polymerization "“showed a significant difference in % transmittance intensity pattern as well as peak area absorption at a wave number of 3,500 cm-1 as "“OH vibration peak and at 1,750 cm-1 as "“C=O carbonyl vibrational peak.